Health Benefits of Improved Latrine in Rural China - Shang, Shibo; Li, Hongxing; Wang, Li; Yao, Wei; Lin, Lin; Zhang, Rong (Frontiers in Environmental Science, 2022)
Proper sanitation facilities promote health because they allow people to dispose of their waste appropriately. Since the founding of the People’s Republic of China, the Chinese government has been committed to improving water and sanitation. The coverage of sanitary latrines in rural China reached more than 70.0% in 2022. Using published literature, open data, and national statistics, this study evaluated the health effects of improved latrines in China. A search strategy aimed at collecting all latrine improvement-related community intervention research in China from 1990 to 2021 was designed and implemented. Incidences of three diseases—schistosomiasis, diarrheal disease, and soil-transmitted helminths (STH)—were used as indicators of health benefits. The relationship between adjusted relative risk (RR) and coverage of sanitary latrines in the study area was examined using a log-linear model. Overall, 411 incidences of the three diseases before and after community intervention were extracted from 74 qualified articles. The results demonstrated the importance of promoting access to sanitary latrines in disease prevention and control in China. The overall estimates revealed mean reductions of 60% for diarrhea risk, 42% for schistosomiasis risk, and 65% for STH risk compared to no intervention. In addition, increasing sanitary latrine coverage was negatively correlated with RR in China, indicating that populations with high sanitary latrine coverage were less likely to be affected with water, sanitation, and hygiene-related diseases.